2017
DOI: 10.1149/2.1361712jes
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Hydrogen Compression: Efficient Pressurization Concept Derived from an Energetic Evaluation

Abstract: Electrochemical hydrogen compression is a potentially high efficient, low-maintenance and silent technology to produce high pressure hydrogen. A new pressure concept with increased compression efficiency, termed intermediate differential pressure polymer electrolyte water electrolysis is proposed. With slightly pressurized oxygen and a much higher hydrogen pressure, this pressure concept profits from the advantages of the lower gas crossover of differential (only hydrogen compressed) pressure water electrolysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 32 publications
(47 reference statements)
0
30
0
2
Order By: Relevance
“…It was shown by Grigoriev et al that for high current densities, the cell voltage can be reduced by increasing the pressure, which is in contradiction to the Nernst equation [32]. This result was approved by Bernt et al [33] and was shown by Suermann et al for the balance pressure mode [21]. This finding relates to enhanced reaction kinetics, which makes j 0 a function of pressure.…”
Section: Hydrogen Production Efficiencymentioning
confidence: 94%
See 1 more Smart Citation
“…It was shown by Grigoriev et al that for high current densities, the cell voltage can be reduced by increasing the pressure, which is in contradiction to the Nernst equation [32]. This result was approved by Bernt et al [33] and was shown by Suermann et al for the balance pressure mode [21]. This finding relates to enhanced reaction kinetics, which makes j 0 a function of pressure.…”
Section: Hydrogen Production Efficiencymentioning
confidence: 94%
“…In this case, four mechanical compression steps can be saved when the storage pressure is 100 bar; the membrane thickness is not given in this work. However, Suermann et al concluded that the use of a Nafion 117 membrane allows a reduction in permeation to low levels, and, hence, a cathode pressure of 100 bar [21]. Moreover, several other studies have been conducted that focus on improving PEM electrolysis system operation and efficiency [22][23][24][25][26].…”
Section: Of 21mentioning
confidence: 99%
“…These characteristic drops of the CDD at the channel outlet are also documented in literature for PEMFCs 16,17 and for electrochemical hydrogen compression. 18 In fuel cells the educt starvation at the outlet of the cell builds up a reaction front, which moves toward the inlet, when the amount of educt is further reduced. Mass transport limitation of oxygen in a PEMFC is considered as the main issue for that phenomenon.…”
Section: Current Density Distribution-in a Preliminary Work The Authorsmentioning
confidence: 99%
“…However, AWEs exhibit poor performance in terms of a slow ramping rate, low partial load range, and low operating pressure compared with proton exchange membrane (PEM) electrolyzers, mainly due to the use of liquid electrolytes, such as KOH, and gas crossover through porous separators . Researches on alkaline anion‐exchange separators have been actively carried out to overcome these problems, but their performance and stability are still much lower than those of their acidic separators . Commercial AWEs employ porous separators such as asbestos, fabric of polyphenylene sulfide (PPS), and composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Researches on alkaline anion-exchange separators have been actively carried out to overcome these problems, but their performance and stability are still much lower than those of their acidic separators. 11,12 Commercial AWEs employ porous separators such as asbestos, fabric of polyphenylene sulfide (PPS), and composite materials. Asbestos is no longer used as a separator due to its carcinogenic properties and its instability at high temperature.…”
mentioning
confidence: 99%